2016
DOI: 10.1016/j.jvs.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Coated Balloon Versus Standard Balloon for Superficial Femoral Artery In-Stent Restenosis: The Randomized Femoral Artery In-Stent Restenosis (FAIR) Trial

Abstract: Conclusion: Drug-coated balloon angioplasty (DCBA) for superficial femoral artery (SFA) in-stent restenosis (ISR) is associated with less recurrent restenosis and a better clinical outcome than plain old balloon angioplasty (POBA) with no apparent differences in safety. Summary: Treatment of femoropopliteal artery stenotic and occlusive lesions has become main stream in recent years. However, many times long term primary patency rates are suboptimal and as a result treatment of ISR has become increasingly impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 0 publications
3
41
0
1
Order By: Relevance
“…Notably, 2 randomized trials comparing 2 different PEB technologies versus BA for ISR of SFA led to inconsistent results. The FAIR (Femoral Artery In‐Stent Restenosis) trial showed a reduction in recurrent restenosis assessed by ultrasound at 6 months and lower risk of TLR at 1 year after a percutaneous therapy with PEB versus BA . In contrast, the PACUBA I (Paclitaxel Balloon Versus Standard Balloon in In‐Stent Restenoses of the Superficial Femoral Artery) trial showed improved primary patency rates but no benefit in terms of TLR at 1 year after a percutaneous therapy with PEB versus BA .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, 2 randomized trials comparing 2 different PEB technologies versus BA for ISR of SFA led to inconsistent results. The FAIR (Femoral Artery In‐Stent Restenosis) trial showed a reduction in recurrent restenosis assessed by ultrasound at 6 months and lower risk of TLR at 1 year after a percutaneous therapy with PEB versus BA . In contrast, the PACUBA I (Paclitaxel Balloon Versus Standard Balloon in In‐Stent Restenoses of the Superficial Femoral Artery) trial showed improved primary patency rates but no benefit in terms of TLR at 1 year after a percutaneous therapy with PEB versus BA .…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of femoral‐popliteal in‐stent restenosis (ISR) is exceptionally challenging due to high rates of reoccurrence. The Femoral Artery In‐Stent Restenosis (FAIR) trial randomized 119 patients with femoral‐popliteal ISR to either DCB ( n = 62) or PTA ( n = 57). These lesions were short to intermediate in length (mean lesion length was 82.2 ± 68.4 mm) with nearly 30% being occlusions and another 25% with moderate to severe vessel calcification.…”
Section: Methodsmentioning
confidence: 99%
“…Patency with DCBs ranged from 70.5% to 92.1% with TLR from 9.2% to 13.6% at 1 year. 3,4,28 Also in intermediate lesions, DES using the Zilver PTX showed patency and TLR rates of 95% and 3.8%, respectively, at 6 months and 78.8% and 19% at 1 year. 29 Combining therapeutic modalities may offer a superior treatment than either device can achieve alone.…”
Section: Discussionmentioning
confidence: 98%
“…21 Treatment of FP ISR with conventional balloon angioplasty carries a higher rate of TLR at 1 year (31% to 47%) and reduced patency rates ranging from 28% to 37%. [1][2][3][4][5] Chronic total occlusion is a strong predictor of loss of patency and a higher TLR in patients with FP ISR following treatment with angioplasty. 22 Several strategies have been attempted to treat FP ISR to improve on angioplasty results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation